Pengaruh Jumlah Objek Wisata, Kualitas Infrastruktur Jalan,Pengeluaran Wisatawan, terhadap Pertumbuhan Ekonomi Antar Provinsi di Indonesia - Gustina Sari; Haikal Rahman; Eko Wahyu Nugrahadi; Dedy Husrizal Syah; Zulkarnain Siregar (Journal of Management and Creative Business, 2026)
This study aims to analyze the effect of the number of tourist attractions, road infrastructure quality, and tourist expenditure on economic growth across provinces in Indonesia. This is a quantitative study using secondary panel data comprising 32 Indonesian provinces as cross-sectional data and the period from 2018 to 2024 as time-series data. The data analysis technique used is Panel Data Regression. Based on the model selection tests (Chow, Hausman, and LM tests), the best estimation model used in this study is the Fixed Effect Model (FEM). The results of the study indicate that: (1) the number of tourist attractions has a positive and significant effect on economic growth; (2) road infrastructure quality has a negative but insignificant effect on economic growth; (3) tourist expenditure has a positive but insignificant effect on economic growth; and (4) simultaneously, the number of tourist attractions, road infrastructure quality, and tourist expenditure have a significant effect on economic growth across provinces in Indonesia. These findings imply that while the addition of tourist attractions can drive economic growth, high tourist expenditure and road quality have not yet directly had an optimal impact on the regional economy, indicating the presence of an economic leakage phenomenon and the need to strengthen local supply chains so that tourist spending is truly enjoyed by the local community.